Application of the Real Options in Engineering Design and Decision Making: Focus on Mine Design and Planning at Operational Level - Ajak, Ajak Duany (Curtin University, 2018)
Flexibility and adaptability are essential for long-term corporate success, and real options (RO) is the preferred tool for analysis. This research argues that uncertainty is a source of value as the opportunities that it presents can be leveraged by having a flexible system. As a contribution to knowledge, a relationship between the beta and flexibility index was derived, RO identification framework for mine operational decision-making was proposed and predictive data analytics was utilised to create managerial flexibility.